QT and P-wave dispersion during the manic phase of bipolar disorder - Gurok, Mehmet Gurkan; Korkmaz, Hasan; Yildiz, Sevler; Bakis, Dilek; Atmaca, Murad (Dove Medical Press Ltd, 2019)
Background and aim: Patients with bipolar disorder (BD) are at increased risk for cardiovascular diseases and complications. This increased risk is considered to be associated with the autonomic nervous system (ANS) abnormalities. However, there is little or no documentation of the relationship between this increased risk and the phases of BD. In this study, we aimed to compare the changes in the QT dispersion (QTd) and P-wave dispersion (Pd), which are predictors of sudden cardiac death and atrial fibrillation, between the patients with manic BD and healthy controls. Participants and methods: The study included a patient group of 44 patients (26 female and 18 male) that were hospitalized due to a diagnosis of manic BD and met the inclusion criteria, and a control group of 34 age- and gender-matched healthy individuals (21 female and 13 male) with no history of psychiatric and neurological disorders. The QTd and Pd values were determined in each participant by performing the standard 12-lead body surface electrocardiography (ECG). Results: The principal electrocardiographic indicators including corrected maximum QT interval, corrected QT dispersion, and minimum P-wave duration significantly increased in the patient group compared to the control group (t=2.815, p<0.01; t=4.935, p<0.001; t=3.337, p<0.001, respectively). Conclusion: The results indicated that patients with manic BD are at increased risk for cardiovascular autonomic dysfunction. Therefore, clinicians should be more careful about ECG changes and related possible cardiac conduction problems such as cardiac arrthythmias in patients with manic BD. Further longitudinal studies are needed to investigate BD and its phases (depression, mania, and hypomania) with regard to ANS and cardiac abnormalities.
Keywords: mania; bipolar disorder; QT dispersion; P-wave dispersion